STRONGER 60+ Adaption of the multimodal FINGER model to prevent cognitive decline in a Swedish primary care rehabilitation unit: An effectiveness‐implementation hybrid design: Prevention (nonpharmacological) / Multidomain. (7th December 2020) - Thunborg, Charlotta; Åkesson, Elisabet; Leavy, Breiffni; Håkansson, Krister; Sindi, Shireen; Solomon, Alina; Levak, Nicholas; Kivipelto, Miia
Abstract: Background: Preventing cognitive and physical decline in people >60 is a major public health priority. Evidence‐based programs for promoting healthy lifestyle in people 60+ are sparse. WHO has launched risk reduction guidelines for cognitive decline and dementia focusing on several lifestyle and cardiovascular risk factors. The FINGER trial is the first large RCT indicating that targeting several risk factors simultaneously can reduce cognitive and functional decline among at risk elderly persons. To develop and implement personalized, effective and feasible lifestyle interventions for real life settings, the multimodal FINGER model needs to be adopted and new evidence from recent studies implemented (e.g. importance of psychosocial factors). The aim of STRONGER 60+ is to adapt the FINGER‐model and investigate intervention effectiveness on lifestyle factors in association with cognitive‐ and physical function. By adopting a hybrid‐design, the implementation process will be followed in a real‐world setting. Method: STRONGER 60+ will include an adapted version of the FINGER‐model, with the components of a brain‐healthy diet, exercise, cognitive training, and stimulating social activity, in addition with careful monitoring of cardiovascular risks. A co‐production design including clinicians and participants will be used. It is a 6‐monh (with 12 month follow‐up) randomized controlled, single blind parallel‐group clinical effectiveness study. Up to 160 persons will be recruited. Participants will receive either the adapted multimodal healthy lifestyle intervention or regular health advice. A measure of psychosocial states will be included to highlight the importance of tailormade interventions in the study. The intervention is designed for community‐dwelling persons ≥ 60 years, with elevated risk for dementia according to the Dementia Risk Tool risk score, MMSE ≥ 24. Result: We are currently finalizing the resource planning, recruitment start in September 2020. With the hybrid‐design outcome evaluation we will be able to explore the process by examining; facilitators and barriers for the adaption process, the recruitment process of participants, the extent to which the target audience encounter the program, retention rate, fidelity to the FINGER‐model, dose received/delivered. Conclusion: For people at‐risk of cognitive‐ and physical decline to benefit from multimodal lifestyle intervention research, interventions tested in research settings require adaption and assessment in real‐world clinical practice.